Kinas intåg på skogsvarumarknaden : idag och i framtiden - Mörner, Gabriel (SLU/Dept. of Forest Products, 2006)
Because of the large economic growth in China there are many companies who have economic interests in the Chinese market. Also in the forest market companies have started to invest in China and the interest for the market is growing. The question is how the Chinese forest market will develop in the years to come? How will China's entry on the market of forest products affect the global forest market?